Hands-On Artificial Intelligence on Amazon Web Services : Decrease the time to market for AI and ML applications with the power of AWS /: Decrease the time to market for AI and ML applications with the power of AWS. (2019) - Tripuraneni, Subhashini; Song, Charles
No abstract available